Most parasite-specific CD8(+) cells in Trypanosoma cruzi-infected chronic mice are down-regulated for T-cell receptor-αβ and CD8 molecules - Grisotto, M G (Blackwell Science Inc, 2001)
The present study shows that CD8(+) T lymphocytes expressing low levels of T-cell receptor (TCR)αβ, CD8 and CD3 accumulate in the spleen, blood, peritoneum and liver, but not in the lymph nodes of mice chronically infected with Trypanosoma cruzi. Analysis of spleen lymphocytes reveals that most CD8(LOW) TCR(LOW) T cells have an experienced phenotype (CD44(HIGH) CD62L(LOW) and CD45RA,B,C(LOW)). These cells have small size, lack activation markers such as CD69, CD25 and CD11b (Mac-1), and do not spontaneously secrete cytokines, suggesting they are at the resting state. When stimulated in vitro with T. cruzi-infected macrophages, TCR(LOW) CD8(LOW) T cells behave as parasite-specific memory cells, readily responding with interferon-γ (IFN-γ) production. Indeed, among parasite-activated CD8(+) lymphocytes, IFN-γ production was mostly due to TCR(LOW) CD8(LOW) cells. Upon in vitro stimulation with anti-CD3/CD28 monoclonal antibodies, down-regulated cells produce IFN-γ and tumour necrosis factor-α, but not interleukin IL-10 or IL-4. Our results indicate that despite parasite persistence, most T. cruzi-specific experienced CD8(+) cells are resting. Nevertheless, when encountering infected macrophages these cells differentiate to Tc1 effectors.